Sustainability of sugarcane bagasse as natural fibre composite products in YIWU communities: a conceptual framework - Xue, Zhang; Hanif Khairi; Syed Mohd Faisal Syed Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2023)
Global warming, white pollution, ecological degradation and other environmental and resource issues have become the focus of attention in all areas of society today, and sustainable development is no longer a slogan. Design practitioners are committed to developing new visions and approaches. The application of materials is an important part of realising a circular economy. Sugar cane is the world's number one sugar crop and the second largest bioenergy crop, while bagasse is one of the most produced agricultural wastes in the world. This study is located in the hometown of brown sugar in China - Yiwu City, Zhejiang Province. The research objective is to develop the design and application of bagasse fibre composites in the brown sugar industry of Yiwu using waste bagasse materials as a starting point. The aim is to use design to drive the circular flow of waste resources, extend the economic chain of the brown sugar industry, and help build a local ecological civilisation and sustainable economic development. The researcher used theoretical framework, qualitative research and data analysis as research methods. In this study, the theoretical framework of sustainable development of the brown sugar industry in Yiwu is proposed, and the circular path diagram of the brown sugar industry ecological park. With theory guiding practice, and successfully developed bagasse paper material and bagasse bioplastic material and applied them in the field of lamps and brown sugar product packaging.